The Role of Social Media in the Formation of Language Politeness of Elementary School Students - Siswanto, Bambang Edi; Wahida, Siska Nur; Habibie, Ramadhan Kurnia; Ika Puspita, Ari Metalin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to describe the role of social media in forming language politeness in elementary school students. The type of research used is a qualitative approach with data sources from students, teachers, and parents. The location of the research was carried out at SDN Semampirejo, Lamongan Regency. Data collection techniques use observation, interviews, and documentation. This model emphasizes that data analysis in qualitative research takes place in a cycle and consists of three main stages: data reduction, data presentation, and drawing conclusions/verification. The results of the study show that social media has a complex influence on students' language politeness. Students tend to maintain language politeness when communicating with teachers and parents, but in interaction with peers, the use of language is more relaxed and follows digital trends. Schools have tried to teach language norms and ethics, but the main challenge is how to shape those habits in student interactions on social media. Environmental factors, including the roles of teachers, parents, and peers, have a major influence on students' communication patterns. In addition, indications of negative behavior, such as profanity and sarcasm in online communication, were found, indicating the importance of further supervision. This study concludes that social media has a dual role in the formation of language politeness. Therefore, collaboration is needed between schools, families, and the surrounding environment to instill the values of politeness in students' digital communication.